Sexual Violence on Campus: Between Power Relations and Law Enforcement - Putra, Akbar Kurnia; Ardianto, Budi; Sipahutar, Bernard; Siregar, Elizabeth (LPPM Universitas Jambi, 2024)
Addressing sexual violence in higher education must be a top priority for several critical reasons. First, it causes serious harm to victims—physically, socially, and psychologically. Second, many incidents go unreported due to stigma or pressure from perpetrators, forcing victims into silence. Third, sexual violence is often normalized and not seen as requiring urgent action. Behaviors like catcalling, loud sexual remarks, whistling, or inappropriate physical contact—such as touching or poking—are frequently overlooked as forms of sexual violence. To tackle this, continuous and structured legal education must be promoted. This is especially vital for partner institutions like undergraduate students at the Midwifery Academy of the Health Polytechnic under the Ministry of Health in Jambi Province. Raising awareness and strengthening understanding of sexual violence prevention should be embedded in educational environments. Additionally, establishing a dedicated task force at Poltekkes Kemenkes Jambi is an essential preventive step. This task force would help ensure a safe and supportive academic atmosphere, where all members of the campus community can participate in learning and other activities without fear of harassment or violence. These efforts aim to build a campus culture that fully rejects and prevents all forms of sexual violence.